2016
DOI: 10.1039/c5ra20492e
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous removal of NH4+-N and refractory organics through sequential heterogeneous Fenton oxidation process and struvite precipitation: kinetic study

Abstract: Graphical representation of integrated HFO and MAP processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Additionally, some inorganic ions like chlorides, carbonates, bicarbonates, and bromides present or generated in degrading organic matter may alter the rate of reaction [15]. Similar experiments were performed by Maharaj et al [7] with synthetic wastewater and observed a maximum COD reduction of 70% at the reaction time of 360 min. Studies were conducted by Perica et al [16] on heterogeneous Fenton in the removal of COD and observed 75% COD removal at 400 min.…”
Section: Fenton Processsupporting
confidence: 58%
“…Additionally, some inorganic ions like chlorides, carbonates, bicarbonates, and bromides present or generated in degrading organic matter may alter the rate of reaction [15]. Similar experiments were performed by Maharaj et al [7] with synthetic wastewater and observed a maximum COD reduction of 70% at the reaction time of 360 min. Studies were conducted by Perica et al [16] on heterogeneous Fenton in the removal of COD and observed 75% COD removal at 400 min.…”
Section: Fenton Processsupporting
confidence: 58%
“…Pre-carbonization and subsequent chemical activation were followed for the preparation nanoporous activated carbon from the raw material, rice husk as detailed by our earlier research work [32][33][34][35]. The functionalization of NPAC was performed with the addition of ethylenediamine to produce amine-modified matrix.…”
Section: Modified Nanoporous Activated Carbon (M-npac) Preparation Amentioning
confidence: 99%
“…The characteristics of nanoporous activated carbon are presented in the supplementary materials 1.1. and the significance of the parameters were discussed in our earlier studies [32][33][34][35]. The effect of time for the immobilisation of amylase was determined by validating the minimum amylase concentration obtained in the medium after the reaction between saline tolerant amylase and m-NPAC.…”
Section: Optimization Studies For Immobilisation Of Amylase Onto M-npacmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Although a variety of physical, 2 chemical, [3][4][5] and biological treatment methods [6][7][8] have been applied for the removal of nutrients, it is desirable to develop a cost-effective method for nutrient removal.…”
Section: Introductionmentioning
confidence: 99%